PENGARUH PENERAPAN STRATEGI PELAKSANAAN KELUARGA TERHADAP KEMAMPUAN KELUARGA MERAWAT PASIEN HALUSINASI DI KOTA JAMBI TAHUN 2017 - Vevi Suryenti Putri; Trimusarofah Trimusarofah (Jurnal Akademika Baiturrahim Jambi, 2018)
Schizophrenic patients 70% have hallucinations. Nursing in caring for patients with hallucinations namely performance strategy execution for individual or family. Family’s performance strategy is one nursing interventions for patients who are rarely hallucinated to the family. This study aimed to determine is there any affect of family’s performance strategy execution toward the ability of family caring hallucinations patients. This is a quantitative research; it used pre experiment method and used one group pretest and posttest design. Samples were 20 respondents. This study was conducted from July 25th – August 10th 2017, data were collected using instruments in the form of interview and observation sheets. Data analized by using t-test. The average ability of families before being given family’s performance strategy with average score (3.75) to be (5.75) after being given family’s performance strategy. There is different of family’s performance strategy execution toward the ability of family caring for hallucinations patients at Jambi city with p-value 0.00 (<0.05). it conclude that there is the effect of family’s performance strategy execuation toward the ability of family caring for hallucinations patients.